Kesiapan Guru SMA Dalam Pembelajaran Bahasa Inggris Daring di Masa Pandemi Covid-19: Pengelolaan Canvas Instructure LMS - Samsul Khabib; Endah Yulia Rahayu; Nunung Nurjati; Wahju Bandjarjani (Universitas PGRI Adi Buana Surabaya, 2021)
This community service implementation aims to give EFL teachers new perspectives on managing the online materials using CI-LMS. The service employs a field observation method. The participants were high school EFL teachers in Sidoarjo district. The activities were a one-day seminar and online training using CI-LMS and WhatsApp group. The results of this study indicate that participants are satisfied with the training provided, but on the other hand, many participants seem not yet ready to use the CI-LMS shortly. CI-LMS is considered an excellent online learning media for developing the teaching and learning system during the COVID-19 pandemic. However, many teachers are not ready to use this platform at this time. For this reason, ongoing assistance to teachers is essential.